COVID-19 among Hospitalized Patients with Diabetes in Karachi: A Single Centre Study - Wasfa Aijaz, Tasnim Ahsan, Babar Pal, Bharta Rani, Paras Imran, Saeeda Fouzia Qasim (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the clinical characteristics, severity, and outcomes of local COVID-19 patients with diabetes. Study Design: Case series Place and duration of study: Orthopedic Medical Institute Hospital, Karachi from 1st September 2020 to 28th February 2021. Methods: One hundred and forty seven COVID-19 positive patients with diabetes and pre-diabetes were enrolled. The patients’ demographic and clinical information specific to COVID-19 and diabetes was collected and analyzed. Results: The mean age of 64.03±11.56 years. The ischemic heart disease (39.9%) and hypertension (74.3%) were the two most prevalent comorbid conditions. The overall mortality rate of 20.3%. Between patients with diabetes receiving steroids and those receiving no steroids, the mean fasting (FBG) and random blood glucose (RBG) were relatively elevated. Glycemic control had no discernible impact on the severity, results, or length of the COVID-19 hospital stay (p>0.05). Conclusion: No significant effect of diabetes millitus control on COVID severity and outcomes, but the altered blood glucose levels suggest a need to define specific targeted intervention for COVID-19 patients with comorbidities, specifically diabetes mellitus. Keywords: COVID-19, Diabetes mellitus, Diabetes control, Outcome